How safe and effective are aclidinium inhalers for patients with chronic obstructive pulmonary disease (COPD)?. Issue 5 (May 2017) - Smith, Kiernan A.; Pejic, Rade N.
Abstract : EVIDENCE‐BASED ANSWER : In moderate‐to‐severe COPD, aclidinium modestly improves quality of life and decreases hospital admissions without any serious adverse events (SOR: A, meta‐analysis of RCTs). Aclidinium also modestly reduces the rate of COPD exacerbations and rescue inhaler use (SOR: B, RCT). Aclidinium improves lung function as well as tiotropium without any difference in adverse events (SOR: B, RCT).